UNIVERSITY OF NOTTINGHAM - Alsairafi, Ahmed (2010)

(untitled)
In this paper we have found that Islamic banks tend to be less efficient and more risky than conventional banks. This is due to unique risks which have cropped up due to the way that Islamic banks function. The Islamic banking industry is evidently under developed and because of that, efficiency in the way Islamic banks function poses to be a problem that needs to be overcome in the future.